Nurslings Of Protestantism: The Questionable Privilege Of Freedom In Charlotte Brontë’s Villette - Mazurek, Monika (Studia Anglica Posnaniensia, 2015)
In Charlotte Brontë’s Villette, a number of foreigners at various points express their amazement or admiration of the behaviour of Englishwomen, who, like the novel’s narrator Lucy Snowe, travel alone, visit public places unchaperoned and seem on the whole to lead much less constrained lives than their Continental counterparts. This notion was apparently quite widespread at this time, as the readings of various Victorian texts confirm – they often refer to the independence Englishwomen enjoyed, sometimes with a note of caution but often in a self-congratulatory manner. Villette, the novel which, similarly to its predecessor, The Professor, features a Protestant protagonist living in a Catholic country, makes a connection between Lucy’s Protestantism and her freedom, considered traditionally in English political discourse to be an essentially English and Protestant virtue. However, as the novel shows, in the case of women the notion of freedom is a complicated issue. While the pupils at Mme Beck’s pensionnat have to be kept in check by a sophisticated system of surveillance, whose main purpose is to keep them away from men and sex, Lucy can be trusted to behave according to the Victorian code of conduct, but only because her Protestant upbringing inculcated in her the need to control her desires. The Catholics have the Church to play the role of the disciplinarian for them, while Lucy has to grapple with and stifle her own emotions with her own hands, even when the repression is clearly the cause of her psychosomatic illness. In the end, the expectations regarding the behaviour of women in England and Labassecour are not that much different; the difference is that while young Labassecourians are controlled by the combined systems of family, school and the Church, young Englishwomen are expected to exercise a similar control on their own.